Infants with extrahepatic biliary atresia: Effect of follow-up on the survival rate at Ege University Medical School transplantation center - Karakoyun, Miray; Baran, Maşallah; Turan, Caner; Kılıç, Murat; Ergun, Orkan; Aydoğdu, Sema (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: Biliary atresia (BA) is the main cause of neonatal cholestasis and the primary reason for infant liver transplants worldwide. It is an obliterative cholangiopathy observed only in children and caused by progressive inflammation and fibrosis of the bile duct. We collaborated with a liver transplantation center to investigate the effects of follow-up in patients with BA. Materials and Methods: Medical records of 99 patients who were diagnosed with BA and monitored at our center from 1990 to 2002 (27 patients) and from 2003 to 2015 (72 patients) were analyzed retrospectively. Patients were evaluated for birth weight; age at jaundice onset; age at alcoholic stool detection; age at the time of Kasai portoenterostomy (KPE), if performed; age at admission to our center; age at liver transplantation; duration between KPE and transplantation; pediatric end-stage liver disease (PELD) scores during transplantation; and growth and developmental status. The periods 1990-2002 and 2003-2015 were defined as phases I and II, respectively. Results: The median age of the patients at presentation to our hospital was 149 (range: 20-730) days during phase I and 61 (range: 28-720) days during phase II. The median age at jaundice onset was 7 days, and the median age at alcoholic stool detection was 15 days. There was no significant difference between phases I and II in terms of age at jaundice onset, age at alcoholic stool detection, or birth weight. Twenty-five (92.5%) of the 27 patients in the phase I group were admitted to our center after undergoing KPE. Forty-four (61.1%) of the 72 patients in the phase II group (median age at the time of KPE: 47 days) were operated at our center. Median ages of the patients at the time of KPE at our center were 67.5 (range: 25-220) and 47 (range: 28-139) days during phases I and II, respectively. The median age of the 28 patients who were transferred from another center was 70 (range: 45-105) days during phase II. Liver transplantation was performed in 55 of 99 patients (55.5%). Significant differences were observed in the age at transplantation, duration between KPE and transplantation, and PELD scores between patients with BA who underwent KPE at our center and who underwent KPE at other institutes from other institutes. Conclusion: These findings demonstrate the importance of a timely diagnosis of BA and undergoing KPE before malnutrition and/or cirrhosis deteriorate the patient’s health. Furthermore, follow-up of patients with BA at a liver transplantation center increased the success of KPE and improved survival rates. Cite this article as: Karakoyun M, Baran M, Turan C, Kılıç M, Ergun O, Aydoğdu S. Infants with extrahepatic biliary atresia: Effect of follow-up on the survival rate at Ege University Medical School transplantation center. Turk J Gastroenterol 2017; 28: 298-302.